Comparison of three types of Indian donkey populations based on morphometric characteristics - Rahul Behl; S K Niranjan; Jyotsna Behl; R K Vijh (Journal of Livestock Biodiversity, 2025)
The three populations of Indian donkeys; Spiti donkeys distributed in Spiti and Yangthang regions of Himachal Pradesh, Sindhi donkey found in Barmer, Jaisalmer and Jodhpur districts of Rajsthan and Brown type donkeys found mainly in Kurnool and Anathapur districts of Andhra Pradesh were characterized and compared to ascertain whether any signiicant diﬀerences exist in these three populations of Indian donkeys in the studied morphometric parameters. The results of the F-test showed that these three populations to be signiicantly diﬀerent (P